2012
DOI: 10.1182/blood-2012-04-420968
|View full text |Cite
|
Sign up to set email alerts
|

High-content live-cell imaging assay used to establish mechanism of trastuzumab emtansine (T-DM1)–mediated inhibition of platelet production

Abstract: Proplatelet production represents a terminal stage of megakaryocyte development during which long, branching processes composed of platelet-sized swellings are extended and released into the surrounding culture. Whereas the cytoskeletal mechanics driving these transformations have been the focus of many studies, significant limitations in our ability to quantify the rate and extent of proplatelet production have restricted the field to qualitative analyses of a limited number of cells over short intervals. A n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
64
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 79 publications
(67 citation statements)
references
References 27 publications
3
64
0
Order By: Relevance
“…However, the mechanism of DM1 release remains elusive as the authors were unable to detect colocalization between the internalized T-DM1 and lysosomal LAMP1 by immunofluorescence. Thon and colleagues reported that T-DM1-induced thrombocytopenia occurred via a mechanism that is both HER2-and FcgRIIa-independent due to the fact that mouse MKs and platelets do not express HER2 and FcgRIIa and that both take up T-DM1 (41). This study suggests that T-DM1 is endocytosed through an alternative pathway (41).…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…However, the mechanism of DM1 release remains elusive as the authors were unable to detect colocalization between the internalized T-DM1 and lysosomal LAMP1 by immunofluorescence. Thon and colleagues reported that T-DM1-induced thrombocytopenia occurred via a mechanism that is both HER2-and FcgRIIa-independent due to the fact that mouse MKs and platelets do not express HER2 and FcgRIIa and that both take up T-DM1 (41). This study suggests that T-DM1 is endocytosed through an alternative pathway (41).…”
Section: Discussionmentioning
confidence: 85%
“…Thon and colleagues reported that T-DM1-induced thrombocytopenia occurred via a mechanism that is both HER2-and FcgRIIa-independent due to the fact that mouse MKs and platelets do not express HER2 and FcgRIIa and that both take up T-DM1 (41). This study suggests that T-DM1 is endocytosed through an alternative pathway (41). Although it is still a matter of debate whether trastuzumab associates with mouse HER2, many laboratories have been using mouse model to investigate the mechanisms of trastuzumab-induced cardiotoxicity, and data from these studies suggest that trastuzumab-…”
Section: Discussionmentioning
confidence: 99%
“…ProPLTs in shear cultures were uniformly extended into the lower channel and aligned in the direction of flow against the vascular channel wall, recapitulating physiological proPLT production 11,30,32 (supplemental Movie 2). The percent of proPLT-producing primary mouse MKs under physiological shear stress were doubled over static cultures 26 to ;90% ( Figure 3D).…”
Section: Resultsmentioning
confidence: 96%
“…Although second-generation cell culture approaches have provided further insight into the physiological drivers of PLT release, they have been unable to recreate the entire BM microenvironment, exhibiting limited individual control of extracellular matrix (ECM) composition, 19,20 BM stiffness, 21 endothelial cell contacts, 22,23 and vascular shear stresses, 24,25 and have been unsuccessful in synchronizing proPLT production, resulting in nonuniform PLT release over a period of 6 to 8 days. 26 Moreover, the inability to reproduce the BM microenvironment ex vivo, and resolve physiological proPLT extension and release by high-resolution live-cell microscopy, has significantly hampered efforts to study the cytoskeletal and signaling mechanics of PLT production. Biomimetic platforms that model human BM are needed to support drug development and establish new treatments for thrombocytopenia.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation